Соціальний інтелект курсантів закладів вищої освіти сектору безпеки та оборони, які отримують вищу освіту за спеціальностями «Право» та «Психологія» - Харченко, С. В.; Kharchenko, S. V.; Колдашов, О. В.; Koldashov, O. V.; Svitlana Kharchenko (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 3 (106). - С. 320-328, 2024)
У статті наведено результати емпіричного дослідження здібностей соціального інтелекту здобувачів вищої освіти закладів вищої освіти сектору безпеки та оборони, які навчаються за спеціальностями «Право» та «Психологія». Показано, що в курсантів, які брали участь у дослідженні, найчастіше діагностували середній рівень соціального інтелекту. У майбутніх психологів у структурі соціального інтелекту найбільш розвиненою виявилась здібність передбачати наслідки поведінки, а у майбутніх юристів – здібність розуміти зміну значення вербальних реакцій людини залежно від контексту ситуації, яка їх викликала.

The article emphasises that for the actors of the security and defence sector, solving various communication situations is a constant and important task which can become difficult to perform if the social intelligence abilities are not sufficiently developed. A comparative analysis of the peculiarities of social intelligence abilities of higher education students of higher education institutions of the security and defence sector, who study in the specialities of “Law” and “Psychology”, was carried out. It is emphasized that the specificity of the social situation of the study participants' intellectual abilities development is due to certain features: lockdowns and quarantines of 2020–2021 with the vast majority of distance education, which were caused by the spread of the COVID-19 virus infection; martial law, which has been in force since February 2022. The senior students of Kharkiv National University of Internal Affairs and the Military Law Institute of Yaroslav Mudryi National Law University took part in the study. The empirical data were obtained using J. Guilford’s psychodiagnostic methodology for studying social intelligence. It has been found that the general level of social intelligence of most of the surveyed cadets corresponded to the average level. It has been shown that the general level of social intelligence of the cadets studying “Psychology” was higher than that of the cadets studying “Law”. It has been revealed that the differences in the level of social intelligence of the surveyed groups of cadets were due to a statistically significantly higher level of development of the ability to predict the consequences of the behaviour of others in typical conditions among cadets studying “Psychology” and a more developed ability to understand the logic of interaction situations and the significance of people's behaviour in these situations. It has been established that the most developed ability of social intelligence of the study participants studying in the speciality “Law” was the ability to understand the change in the meaning of similar verbal reactions of a person depending on the context of the situation that caused them. It has been argued that the specific social conditions of personality formation of higher education students in recent years have not significantly affected the level of development of their social intelligence abilities. The main directions of development of social intelligence abilities of cadets studying in different specialities are presented.

В статье приведены результаты эмпирического исследования способностей социального интеллекта соискателей высшего образования учреждений высшего образования сектора безопасности и обороны, обучающиеся по специальностям "Право" и "Психология". Показано, что у участвовавших в исследовании курсантов чаще всего диагностировали средний уровень социального интеллекта. У будущих психологов в структуре социального интеллекта наиболее развитой оказалась способность предвидеть последствия поведения, а у будущих юристов – способность понимать изменение значения вербальных реакций человека в зависимости от контекста вызвавшей их ситуации.
Social intelligence of cadets of the security and defence sector higher education institutions who receive higher education in the specialities of “Law” and “Psychology”
Keywords: соціальний інтелект; здібності соціального інтелекту; рівень розвитку соціального інтелекту; здобувачі вищої освіти ЗВО сектору безпеки та оборони; методика дослідження соціального інтелекту Дж. Гілфорда; social intelligence; social intelligence abilities; level of development of social intelligence; higher education students of the security and defence sector; J. Guilford’s methodology for studying social intelligence; социальный интеллект; способности социального интеллекта; уровень развития социального интеллекта; соискатели высшего образования ЗВО сектора безопасности и обороны; методика исследования социального интеллекта Дж. Гилфорда